Impact and future of artificial intelligence - Lopes da Costa, R.; Diamantino, J.; Pereira, L.; Dias, Á.; Gonçalves, R.; Teixeira, N. (International Journal of Services, Economics and Management, 2022)
The current business context is marked by a regular transformation that involves all sectors, which means that not only companies but also people have to adapt to new realities, having as main purposes the maximum efficiency and motivation of workers. If, in one hand, the main purpose of creating and using artificial intelligence (AI) tools came to make people's lives easier, in the other hand their use with no control may bring bad consequences. We have used a mixed method - interviews and quiz. The results of this research have contributed for managers and other national entrepreneurs to become aware of the main advantages, risks, concerns and doubts of the use of AI. It was also possible to determine which areas are AI currently present in, as well as the potentially most advantageous sectors in the short term, where AI can be used.